Packaging and Storage of Hops (Humulus lupulus) - Sean M. Campbell; Brian J. Pearson (EDIS, 2018)
Hops (Humulus lupulus) are an essential ingredient to the production of beer. This 3-page document describes how to properly store and package hops. Written by Brian Pearson and Sean Campbell and published by the UF/IFAS Environmental Horticulture Department, June 2018. https://edis.ifas.ufl.edu/ep561